Evaluation of delay factors on dry bulk cargo operation in Malaysia: a case study of Kemaman Port - Abdul Rahman, Noorul Shaiful Fitri; Othman, Mohammad Khairuddin; Sanusi, Izzat Amir; Md Arof, Aminuddin; Ismail, Alisha (2019)
There are various types of delay factors that could affect the efficiency and effectiveness of the dry bulk cargo operation, especially in port. Hence, it raises the concerns of the stakeholders, as some of them can significantly affect their actual transport plans and cost them extra money to handle the cargo. Due to uncertainty of the most significant delay factor in some Malaysia's dry bulk ports, therefore, this study aims to evaluate the most significant delay factors that causing delays in dry bulk cargo operation by using the analytical hierarchy process (AHP) method. This study found that the factor of ‘Miscellaneous’ is the most significant factor that contributed to the most of delay creations in dry bulk cargo operation in Kemaman port. Meanwhile, sub-criterion of ‘Foul weather and tide prediction’ is selected as the most significant sub-cause of delay creation in similar port. This study contributes the practical technique and valuable findings to the port and its stakeholders, where it may alert the them to measure the factors that affect their operational performance and business. Also, it introduces the usage of practical and systematical analysis technique for assisting the seaport operator or interested parties in analyzing the potential contributors of a condition in the port settings.